Histopathological Evaluation of Surgically Treated Renal Lesions - Singla, Disha; Rathod, Gunvanti (Annals of Pathology and Laboratory Medicine, 2018)
Background: Nephrectomy is a common procedure in surgical practice. It is indicated in patients presenting with symptomatic chronic infections, obstruction, calculus disease, and severe traumatic injury to renal cell carcinomas. Methods: The present study was conducted in the Department of Pathology and included all nephrectomy specimens received in the department over a period of five years (January 2011 - December 2015). Patient particulars were recorded, which included age, sex, chief complain and clinical findings; investigations such as CT scan, USG, and other relevant investigations were also noted. Meticulous histopathological examination was done and diagnosis was given. Result: Total 124 patients underwent nephrectomy for various renal lesions in the last 5 years. There were 93 (75%) male and 31 (25%) female patients. In 12 patients, tumor was diagnosed on routine abdominal ultrasonographic screening for some other complains. Flank pain was the most common presenting symptom observed in 76 (61.29%) patients, followed by hematuria in 22 (17.54%) patients. On histopathological examination, 94 (75.80%) were non-neoplastic renal lesions and 30 (15.20%) were tumors. In non-neoplastic lesions of total nephrectomy specimens chronic pyelonephritis 70 (56.46%) was the most common type of lesions followed by pyonephrosis 9 (7.26%). There was also presence 4 (3.23%) of cases of Tuberculosis kidney. Overall, RCC was the most common 20 (16.13%) renal tumor. Conclusion: The present study provides a fair insight into the histological patterns of lesions in nephrectomy specimens in our institution and its correlation with studies conducted across the world.